Glycerol in subcritical and supercritical solvents. Issue 1 (14th October 2016) - Galy, Nicolas; Nguyen, Rémi; Yalgin, Hasret; Thiebault, Nicolas; Luart, Denis; Len, Christophe
ABSTRACT: Glycerol conversion to added value chemicals is a research avenue that has attracted significant interest in recent years. The utilization of critical solvents such as water and organic solvents in critical conditions as well as subcritical conditions (or hot compressed solvent) and supercritical conditions can offer several advantages to batch processes and in continuous flow systems in view of their potential implementation in industry. This review has been aimed to highlight most recent key processes for glycerol valorization to valuable products using different types of catalysts and processes. © 2016 Society of Chemical Industry